KONSEP ISTIṬĀ’AH DALAM AL-QUR’AN PADA IBADAH HAJI - Ahmad Bahrin Nada (Jurnal Tafsere, 2019)
Worship to Allah is an obligation for each individual as proof of obedience to the creator, with the existence of the Islamic shari'a the religious community has been arranged in such a way that in performing their worship to God optimally and in accordance with their capacities. So that in the guidance of the Islamic religion the context of istiṭā'ah becomes a matter that needs to be considered and applied, as Islam is a flexible religion towards its followers. The concept of istiṭā'ah is the basic foundation for the application of Islamic shari'a, especially in the Hajj, so that Muslims who are not yet classified as istiṭā'ah are not obliged to go on Hajj and are not recommended to try in various ways to be able to perform the Hajj. so that with the concept of istiṭā'ah if it is implemented by the Indonesian government in a complex way to implement current study regulations, it will greatly minimize the problem of studies that make the Indonesian Muslim community restless with the unstoppable waiting list so that new negative effects arise due to the madharat caused from financial inability to register for Hajj.